Pengaruh Kepemimpinan Terhadap Motivasi dan Kinerja Karyawan pada Direktorat Jendral Administrasi dan Keuangan, Kementerian Estatal Timor Leste - Bonaparte do Rêgo, Elvino; Supartha, Wayan Gede; Kerti Yasa, Ni Nyoman (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2017)
Employee performance is one of the determinant factors for the achievement of organizational performance. Therefore, improving employee performance is an important issue that must be considered. Many factors can affect employee performance, such as: leadership and motivation. Based on the existing issues in the Directorate of Administration and Finance Ministry Genderal Estatal East Timor, this study examines three variables, namely: leadership, motivation, and performance of employees. The purpose of this study was to determine the effect of leadership on motivation and performance of employees in the Directorate of Administration and Finance Ministry Genderal Estatal East Timor. The population in this study were all employees of the Directorate of Administration and Finance Ministry Genderal Estatal Timorese by the number of employees as many as 152 people, while the sample is 110 by using a sampling technique proportionate stratified random sampling. The data used are primary data and secondary data with the questionnaire data collection methods. The analysis tool is used path analysis. The results obtained in this study are positive and significant effect of leadership on the motivation, meaning that if the leadership is getting better, then the increased work motivation. Motivation has a positive and significant impact on the performance of employees, meaning that if the motivation is getting better, then the performance of employees is increasing. Leadership has a positive and significant impact on the performance of employees, meaning that if the leadership is getting better, then the performance of employees is increasing. Therefore, in the future to improve the performance of employees, the Directorate of Administration and Finance Ministry Genderal Estatal Timorese leadership should develop in order to get better and improve employee motivation.